An outbreak of severe invasive meningococcal disease due to a capsular switched Neisseria meningitidis hypervirulent strain B:cc11. (January 2019) - Stefanelli, P.; Fazio, C.; Vacca, P.; Palmieri, A.; Ambrosio, L.; Neri, A.; Piana, A.; Castiglia, P.; Argiolas, F.; Santus, S.; Masala, L.; Steri, G.; et al.
Abstract: Objectives: The aim was to investigate an outbreak of invasive meningococcal disease (IMD) in Southern Sardinia. Methods: Epidemiological and microbiological investigations were performed. The latter included antimicrobial susceptibility testing and whole-genome sequencing (WGS). Results: Seven individuals with severe IMD were found to be infected with serogroup B (MenB) Neisseria meningitidis in the first quarter of 2018. Five of the seven cases (five males; mean age 19 years; range 18–21 years; CFR 40%) were due to a unique strain B:P1.5-1, 10-8:F3-6:ST-11(cc11), probably switched from the hypervirulent C-cc11, as confirmed by WGS. All five patients had attended the same nightclub in the 2 weeks prior to symptom onset. Public health measures, including chemoprophylaxis of contacts and active immunization against MenB, were implemented. Conclusions: We observed five IMD cases due to the same switched MenB strain. The hypervirulent B:P1.5-1, 10-8:F3-6:ST-11(cc11) strain, probably switched from C-cc11, is of concern due to the observed high virulence and case fatality rates. All the patients shared the same place of probable exposure. The molecular characterization of the invasive strain allowed the outbreak to be confirmed, which was then controlled through timely public health action.